CBN reinforced NiCrAlY metal ceramic composite powder on surface of high-temperature component, coating and preparation method of cBN reinforced NiCrAlY metal ceramic composite powder
NiCrAlY-cBN cermet composite powder was prepared by high-energy ball mill mechanical alloying method, which solved the problem of uneven component distribution in the metal cermet powder spray coating, and achieved uniform distribution and performance improvement of the surface coating of high-temperature components.
Patent Information
- Application Number
- CN202411959692.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the coating prepared by metal cermet powder spraying prepared by mechanical mixing method, the metal phase and ceramic phase components are unevenly distributed, which limits the strength and toughness of the metal phase and the wear and corrosion resistance of the ceramic phase.
NiCrAlY-cBN cermet composite powder was prepared by high-energy ball mill mechanical alloying method. Ball milling was performed under argon environment and a powder of 15-60 μm was obtained through a sieve machine to ensure that the cBN ceramic phase was evenly dispersed in the NiCrAlY matrix phase.
The uniform distribution of metal cermet composite powder is achieved, the problem of uneven powder composition in traditional mechanical mixing methods is overcome, the anti-oxidation and wear resistance of the composite coating is improved, and the service life of high-temperature components is extended.
Smart Images

Figure CN119747668A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal ceramic high temperature protective coatings, and in particular to a cBN reinforced NiCrAlY metal ceramic composite powder and coating on the surface of a high temperature component and a preparation method thereof. Background Art
[0002] Modern industrial equipment such as metallurgy and chemical industry has been in service for a long time in high temperature environment, such as conveyor rollers in continuous annealing line of strip steel, surface of rotary joints on converter, sinking rollers in hot dip galvanizing unit, etc., and the operating temperature can be as high as 700℃. The problems faced by high temperature components in harsh environments such as high load and high temperature for a long time are as follows: 1) The equipment needs to maintain stable mechanical properties in high temperature environment during production operation; 2) Friction and wear in high temperature environment; 3) Surface high temperature oxidation leads to surface structure failure of components; 4) Corrosion in high temperature working environment in metallurgy and chemical industry. These problems affect the normal operation of equipment, and in serious cases affect the quality stability of products, greatly shorten the service life of high temperature components, and even bring hidden dangers to production safety.
[0003] MCrAlY alloy (M refers to Ni, Co, etc.) has good high-temperature oxidation resistance at high temperatures, especially in the range of 900℃ to 1150℃, so it has important research significance in the field of protective coatings for high-temperature components and is often used as the matrix phase of metal ceramic coatings. However, the wear resistance of the coating is relatively weak, and the shortcomings of MCrAlY alloy in this regard can be improved by adding ceramic reinforcement phases. In the current research on reinforcement phases, carbide ceramics are prone to decarburization and decomposition at high temperatures; oxide ceramics cause the coating to peel off because of the mismatch between their thermal expansion coefficient and the metal phase. As a strengthening material, cBN ceramics have high hardness (9MH), high melting point (2973℃), high thermal conductivity (1300W / mK), and low density (3.44g / cm 3 ), low thermal expansion coefficient (3.5×10 -6 / K), and good antioxidant properties. NiCrAlY alloy coating has excellent antioxidant properties, but its hardness is low and its wear resistance is poor. Adding cBN to NiCrAlY can increase the hardness and wear resistance of the coating without affecting its antioxidant properties. At present, in addition to directly using commercial powders, the commonly used method for independently preparing metal ceramic powders is mainly the mechanical mixing method. However, the coating obtained by spraying the metal ceramic powder prepared by the mechanical mixing method has a clear interface between the metal phase and the ceramic phase and an uneven distribution of components, which seriously limits the strength and toughness of the metal phase and the wear and corrosion resistance of the ceramic phase.
[0004] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of uneven distribution of metal phase and ceramic phase components in a coating prepared by spraying a metal ceramic powder prepared by a mechanical mixing method, and provide a cBN-reinforced NiCrAlY metal ceramic composite powder, a coating and a preparation method thereof for a high-temperature component surface.
[0006] In order to achieve the above object, the present invention discloses a method for preparing cBN-reinforced NiCrAlY metal ceramic composite powder on the surface of a high-temperature component, comprising the following steps:
[0007] S1, uniformly mixing NiCrAlY and cBN powders according to proportion;
[0008] S2, ball milling the mixed powder obtained in step S1 under an argon environment;
[0009] S3, the powder obtained after ball milling in step S2 is passed through a sieving machine to obtain NiCrAlY-cBN metal ceramic powder with a size of 15 to 60 μm.
[0010] In step S1, the particle size of NiCrAlY powder is 15-45 μm, wherein the mass percentage of elements is Cr 10-30%, Al 10-20%, Y 0.5-1%, and the balance is Ni; the particle size of cBN powder is 1-3 μm, and its purity is ≥99.5%.
[0011] In step S1, the mass ratio of NiCrAlY to cBN powder is 9-7:1-3, the mixing speed is 60r / min, and the mixing time is 2h. If the mass ratio of NiCrAlY to cBN powder is too small, the particle size range is too large and cannot be sprayed; if the mass ratio is too large, the ceramic phase cannot be evenly distributed in the metal phase, and part of the ceramic phase cannot enter the metal phase.
[0012] In the step S2, the powder of NiCrAlY and cBN is mixed and added to a steel ball mill jar for alloying by high-energy ball milling in a ball mill; GCr15 steel grinding balls are used for ball milling, and the grinding balls are selected according to diameters of 15 mm, 10 mm, 6 mm, and 5 mm, and are prepared into mixed grinding balls in a mass ratio of 1:4:2:1; the mass ratio of the grinding balls to the powder in the jar is maintained at 10:1; the pressure of the vacuum pump connected to the ball mill jar is set to 10 Pa, the time is maintained for 10 min, and argon gas is inflated at a pressure of 0.12 MPa for 3 min, and the cycle is repeated 3 times.
[0013] The parameters of the ball mill are: a rotation speed of 220 rpm and a ball milling time of 50 to 60 h.
[0014] The invention also discloses cBN-reinforced NiCrAlY metal ceramic composite powder on the surface of a high-temperature component prepared by the preparation method.
[0015] The present invention also discloses a cBN-reinforced NiCrAlY metal ceramic composite coating on the surface of a high-temperature component made by using the metal ceramic composite powder. The NiCrAlY-cBN metal ceramic composite coating has a thickness of 150 to 200 μm and a hardness of 600 to 770 HV. 0.3 The porosity of the coating is 0.28-0.45%.
[0016] The present invention also discloses a method for preparing the above-mentioned cBN-reinforced NiCrAlY metal ceramic composite coating on the surface of the high-temperature component, comprising the following steps:
[0017] (1) Before spraying, the surface of the high-temperature component substrate is degreased and cleaned, and then the surface is sandblasted and roughened;
[0018] (2) When using the supersonic flame spraying technology of the oxygen-kerosene system as a coating preparation method, the surface of the sprayed substrate should first be preheated by air spraying, and then the metal-ceramic composite powder should be sprayed to form a NiCrAlY-cBN metal-ceramic composite coating on the surface of the component.
[0019] In the step (1), the sandblasting material is brown corundum sand with a particle size of 25 mesh, the sandblasting pressure is 0.5 MPa, and the surface roughness of the substrate after sandblasting is 5.4-6.0 μm.
[0020] In step (2), the process parameters of the oxygen-kerosene system are: oxygen flow rate 53m 3 / h, kerosene flow rate is 28-32L / h, spraying distance is 340mm, spraying step is 3mm, spraying speed is 800mm / s, powder feeding rate is 30g / min, substrate preheating temperature is 80-120℃.
[0021] Compared with the prior art, the beneficial effects of the present invention are:
[0022] 1. The metal-ceramic composite powder prepared by high-energy ball milling mechanical alloying method has a nearly spherical shape, which makes the powder have a certain fluidity and uniform powder particle size. The cBN ceramic phase is evenly dispersed in the NiCrAlY matrix phase, overcoming the shortcomings of mechanical mixing of powder metal phase and ceramic phase obtained by traditional mechanical mixing method, and uneven distribution of metal phase and ceramic phase in the spray layer;
[0023] 2. The composite coating prepared by the present invention has good anti-oxidation and wear resistance at a high temperature of 700°C, thereby improving the service life of mechanical parts in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a schematic diagram of the step-by-step mechanical alloying process of the present invention;
[0025] Figure 2 The morphology of NiCrAlY-cBN composite powders prepared by the step-by-step mechanical alloying process, where (a) is the powder ball-milled for 50 h, (b) is the powder ball-milled for 55 h, and (c) is the powder ball-milled for 60 h.
[0026] Figure 3 The cross-sectional morphology and EDS composition results of the corresponding points of NiCrAlY-cBN composite powder prepared by the step-by-step mechanical alloying process, where (a) is the powder ball-milled for 50 hours, (b) is the powder ball-milled for 55 hours, and (c) is the powder ball-milled for 60 hours.
[0027] Figure 4 The particle size distribution and average particle size of NiCrAlY-cBN composite powder prepared by step-by-step mechanical alloying process, where (a) is the powder ball-milled for 50 hours, (b) is the powder ball-milled for 55 hours, and (c) is the powder ball-milled for 60 hours;
[0028] Figure 5 The surface and cross-sectional morphologies of NiCrAlY-cBN composite coatings prepared at different kerosene flow rates, where (a) is 28 L / h, (b) is 30 L / h, and (c) is 32 L / h;
[0029] Figure 6 The surface morphology of the friction area and non-friction area of the NiCrAlY-cBN composite coating prepared by the supersonic flame spraying process under 700°C environment and the comparison with the wear rate of the NiCrAlY coating at 700°C, wherein (a) is the wear scar surface, (b) is the oxidized surface, and (c) is the comparison with the wear rate of the NiCrAlY coating. DETAILED DESCRIPTION
[0030] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0031] Example 1
[0032] like Figure 1 As shown, according to the mechanical alloying process,
[0033] S1, first weigh NiCrAlY powder and cBN powder in a mass ratio of 9:1 (NiCrAlY 180g, cBN 10g) and place them in a premixer to mix for 2h. After mixing, take them out and pour them into a stainless steel ball mill, and put the grinding balls in a ratio of 10:1 to the powder mass ratio. The grinding balls are configured in a mass ratio of 15mm:10mm:6mm:5mm=1:4:2:1. Then fill the ball mill with argon, set the vacuum pump pressure to 10Pa, connect the ball mill for 10min, and inflate with argon at a pressure of 0.12MPa for 3min, and cycle 3 times. Use dry grinding method for ball milling, set the speed to 220rpm, and the time is 50h.
[0034] S2, after the ball milling alloying is completed, the composite powder is taken out and the metal ceramic composite powder is sieved. The powder is sieved using a metal sieve with a mesh size of 15 μm and 60 μm to obtain a NiCrAlY-cBN metal ceramic powder with a particle size distribution of 15 to 60 μm.
[0035] The preparation method of NiCrAlY-cBN composite coating for high temperature protection of high temperature parts surface mainly includes the following steps:
[0036] (1) Before spraying, use cleaning powder, alcohol or acetone to degrease the surface of high-temperature parts, and then sandblast the degreased surface for cleaning and roughening. The sandblasting material is 25-mesh brown corundum sand, and the air valve is adjusted to maintain the sandblasting pressure at 0.5MPa. The surface roughness of the substrate after sandblasting is 5.4-6.0μm.
[0037] (2) Turn on the power supply, gas circuit switch and cooling water switch of the spraying equipment, use oxygen as the combustion aid, kerosene as the fuel, and nitrogen as the powder carrier gas, fix the sample on the workbench, and modify the robot arm operation program so that the spraying distance reaches 340 mm, the spraying speed is 800 mm / s, and the spraying step is 3 mm.
[0038] (3) Adjust the kerosene and oxygen flow valves to adjust the oxygen flow rate to 53m 3 / h, kerosene flow rate is 32L / h, kerosene flame flow is ignited to preheat the substrate surface, so that the surface temperature reaches 80-120℃, the powder feeder switch is turned on, and the composite powder that has been ball-milled and alloyed for 50h is delivered to the supersonic spray system, so that the powder feeding rate is maintained at 30g / min. After each 3 sprayings, the coating surface is purged and cooled with an air gun, and the coating thickness is measured with a spiral micrometer. When the coating temperature drops to about 70℃, the spraying equipment is started to continue spraying, and the operation is repeated to finally make the coating thickness reach about 180μm.
[0039] Example 2
[0040] The difference between this embodiment and embodiment 1 is that the dry milling time in step S1 is 55 hours, and the processes of other steps are the same as those in embodiment 1.
[0041] Example 3
[0042] The difference between this embodiment and embodiment 1 is that the dry milling time in step S1 is 60 hours, and the processes of other steps are the same as those in embodiment 1.
[0043] Example 4
[0044] The difference between this embodiment and embodiment 1 is that the kerosene flow rate in step (3) is 28 L / h, and the processes of other steps are the same as those in embodiment 1.
[0045] Example 5
[0046] The difference between this embodiment and embodiment 1 is that the kerosene flow rate in step (3) is 30 L / h, and the processes of other steps are the same as those in embodiment 1.
[0047] Comparative Example
[0048] In this comparative example, commercial NiCrAlY powder was used to prepare the NiCrAlY coating by supersonic flame spraying. The specific steps of supersonic flame spraying were the same as the steps for preparing the NiCrAlY-cBN composite coating in Example 1.
[0049] 1. Performance testing and screening of NiCrAlY-cBN composite powders prepared in Examples 1 to 3
[0050] In the optimal ball milling time region, three nodes of 50 h, 55 h, and 60 h were selected as sample powders. After the powders were prepared, the particle state of the composite powders was observed, such as Figure 2 As shown in the figure, the particles are in a clustered shape with fluidity, and the morphology meets the requirements of thermal spray powder delivery. Figure 3 , 4 The phase distribution of the powders is shown in the figure. The phase distribution of the composite powder after 50 hours of alloying is more uniform, and the average particle size is the largest. The cBN phase of the powder after alloying for less than 50 hours is distributed on the surface of the sphere, and the diameter of the powder after alloying for more than 60 hours is too large. The composite powder after 50 hours of ball milling time is selected as the best spray powder.
[0051] II. Performance testing and screening of NiCrAlY-cBN composite coatings and NiCrAlY coatings prepared in Examples 1, 4, 5 and Comparative Examples
[0052] like Figure 5As shown in the figure, the coatings prepared at 28, 30, and 32 L / h kerosene flow rates are selected as examples, and the three NiCrAlY-cBN composite coatings are named K1, K2, and K3. Comparing the cross-sectional phase layout of the K1, K2, and K3 coatings, the phase distribution of the K3 coating is more uniform, and the black cBN ceramic phase is distributed throughout the coating. Uniform phase distribution can maintain the stability of the coating performance.
[0053] The microhardness of the coating was tested using a small load Vickers hardness tester with a load of 2.94 N and a loading time of 15 s. Fifteen points were tested for each coating and the average value was taken as the microhardness value of the coating. The test results are shown in Table 1.
[0054] Table 1 Microhardness of NiCrAlY-cBN composite coating and NiCrAlY coating prepared in Examples 1 and 2
[0055]
[0056] Example 1, Comparative Example The high temperature wear performance test method of the NiCrAlY-cBN composite coating and the NiCrAlY coating prepared in the following manner:
[0057] The UMT TriboLab high temperature ball-disc friction and wear module was used to perform high temperature wear tests on the K3 NiCrAlY-cBN composite coating and the NiCrAlY coating. The test conditions were a load of 10N, a temperature of 700°C, a friction radius of 4mm, and a wear time of 60min. The coating pair grinding balls used Si3N4 ceramic balls with a diameter of 6.35mm. After the high temperature friction test, the RtecUP Series white light interferometer was used to scan the wear scars of the coating and calculate the wear volume of the coating, and then the coating wear rate was calculated according to the wear rate formula.
[0058] The wear rate formula is: W = V / PL, V = πdS, V is the wear volume (m 3 ), d is the wear scar track diameter (m), S is the wear scar cross-sectional missing area calculated by integrating the fitting data using Origin software (m 2 ), P is the wear load (N), L is the wear distance (m). The composite coating after 700℃ wear and the calculated results are shown in Figure 6 As shown, the non-wear area is not covered by an obvious oxide layer, and the cBN particles are clearly observed to be distributed in the coating, and the surface O content is below 4%. Compared with the NiCrAlY coating, the NiCrAlY-cBN composite coating prepared in Example 1 has a lower wear rate at a high temperature of 700°C, and the addition of cBN ceramics makes it have better wear resistance.
[0059] Figure 6The EDS results of the medium friction area and the non-friction area are compared as shown in Table 2.
[0060] Table 2 Figure 6 Comparison of EDS results of corresponding points on the surface of medium friction area and non-friction area
[0061] Element symbol(wt%) O Ni Cr Al B N 1 26.47 49.79 18.13 5.62 - - 2 4.89 64.49 24.75 5.03 - - 3 2.46 68.25 25.45 3.84 - - 4 3.96 59.63 23.82 4.75 1.75 5.37
[0062] In summary, the NiCrAlY-cBN composite coating for high-temperature protection of high-temperature components prepared by the present invention meets the requirements of high-temperature oxidation resistance and high-temperature wear resistance of mechanical high-temperature components. By improving the process flow, the best powder and coating preparation process is obtained. A metal ceramic composite powder with a mass ratio of NiCrAlY powder to cBN powder of 9:1 is prepared by mechanical alloying process; the spraying process parameters are kerosene flow rate of 32L / h and oxygen flow rate of 53m / h. 3 / h, spraying distance is 340mm, spraying step is 3mm, spraying speed is 800mm / s, powder feeding rate is 30g / min. The composite coating prepared under this parameter has good high temperature wear resistance.
[0063] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. A method for preparing cBN-reinforced NiCrAlY metal ceramic composite powder for high-temperature component surface, characterized in that: The following steps are involved: S1, uniformly mixing NiCrAlY and cBN powders according to proportion; S2, ball milling the mixed powder obtained in step S1 under an argon environment; S3, the powder obtained after ball milling in step S2 is passed through a sieving machine to obtain NiCrAlY-cBN metal ceramic powder with a size of 15 to 60 μm.
2. The method for preparing a high-temperature component surface cBN-reinforced NiCrAlY metal ceramic composite powder according to claim 1, characterized in that: In step S1, the particle size of NiCrAlY powder is 15-45 μm, wherein the mass percentage of elements is Cr 10-30%, Al 10-20%, Y 0.5-1%, and the balance is Ni; the particle size of cBN powder is 1-3 μm, and its purity is ≥99.5%.
3. The method for preparing a cBN-reinforced NiCrAlY metal ceramic composite powder for a high-temperature component surface according to claim 1, characterized in that: In the step S1, the mass ratio of NiCrAlY to cBN powder is 9-7:1-3, the mixing speed is 60 r / min, and the mixing time is 2 h.
4. The method for preparing a cBN-reinforced NiCrAlY metal ceramic composite powder for a high-temperature component surface according to claim 1, characterized in that: In the step S2, the powder of NiCrAlY and cBN is mixed and added to a steel ball mill jar for alloying by high-energy ball milling in a ball mill; GCr15 steel grinding balls are used for ball milling, and the grinding balls are selected according to diameters of 15 mm, 10 mm, 6 mm, and 5 mm, and are prepared into mixed grinding balls in a mass ratio of 1:4:2:1; the mass ratio of the grinding balls to the powder in the jar is maintained at 10:1; the pressure of the vacuum pump connected to the ball mill jar is set to 10 Pa, the time is maintained for 10 min, and argon gas is inflated at a pressure of 0.12 MPa for 3 min, and the cycle is repeated 3 times.
5. The method for preparing a cBN-reinforced NiCrAlY metal ceramic composite powder for a high-temperature component surface as claimed in claim 4, characterized in that: The parameters of the ball mill are: a rotation speed of 220 rpm and a ball milling time of 50 to 60 h.
6. A cBN-reinforced NiCrAlY metal ceramic composite powder for the surface of a high-temperature component prepared by the preparation method according to any one of claims 1 to 5.
7. A cBN-reinforced NiCrAlY metal-ceramic composite coating on the surface of a high-temperature component made from the metal-ceramic composite powder according to claim 6, characterized in that: The NiCrAlY-cBN metal ceramic composite coating has a thickness of 150 to 200 μm and a hardness of 600 to 770 HV. 0.3 The porosity of the coating is 0.28-0.45%.
8. A method for preparing a cBN-reinforced NiCrAlY metal ceramic composite coating on a high-temperature component surface as claimed in claim 7, characterized in that: The following steps are involved: (1) Before spraying, the surface of the high-temperature component substrate is degreased and cleaned, and then the surface is sandblasted and roughened; (2) When using the supersonic flame spraying technology of the oxygen-kerosene system as a coating preparation method, the surface of the sprayed substrate should first be preheated by air spraying, and then the metal-ceramic composite powder should be sprayed to form a NiCrAlY-cBN metal-ceramic composite coating on the surface of the component.
9. The method for preparing a cBN-reinforced NiCrAlY metal ceramic composite coating on a high-temperature component surface as claimed in claim 8, characterized in that: In the step (1), the sandblasting material is brown corundum sand with a particle size of 25 mesh, the sandblasting pressure is 0.5 MPa, and the surface roughness of the substrate after sandblasting is 5.4-6.0 μm.
10. The method for preparing a cBN-reinforced NiCrAlY metal ceramic composite coating on a high-temperature component surface according to claim 8, characterized in that: In step (2), the process parameters of the oxygen-kerosene system are: oxygen flow rate 53m 3 / h, kerosene flow rate is 28-32L / h, spraying distance is 340mm, spraying step is 3mm, spraying speed is 800mm / s, powder feeding rate is 30g / min, substrate preheating temperature is 80-120℃.
Citation Information
Patent Citations
Dysprosia stabilized zirconia abradable
CN101125753A
Nano ZrB2 reinforced CoNiCrAlY metal ceramic composite powder on surface of high-temperature furnace roller, coating and preparation method thereof
CN115780813A
Determination method of flame-resistant and abradable composite coating and flame-resistant and abradable composite coating
CN118854209A
Dysprosia stabilized zirconia abradable
US20080124548A1